Ugotavljanje pretočnih motenj v mikrocirkulaciji pri sladkornih bolnikih z lasersko-doplerskim merilnikom pretokov - Mlačak, Blaž (Zdravniški vestnik, 2003)
Background. The aim of this study was to investigate patients with non-insulindependent diabetes by laser Doppler flowmetry in order to asses changes in the peripheral flow regulation during hemodynamics tests as evidence of impaired auto-regulation of the microcirculation. Methods. 2 groups of subjects were incorporated in the study. The first group included 20patients with diabetes without electromyographical signs of neuropathy and without peripheral arterial occlusive disease while the second (control) groupincluded 20 healthy subjects. Microcirculation investigations were carried out at rest and after hemodynamics tests. Blood flow was measured using a laser Doppler flowmetry. Changes in the flow minus the "biological zero" value were measured after 3 minutes of artificial arterial occlusion, after deep inspiration and by experimental venous hypertension (40 and 70 mm Hg) which was used to provoke venoarteriolar reflex. Results. Resting flow wassignificantly higher in diabetic patients compared to the healthy subjects (p < 0.01). The vasoconstrictor response to deep inspiration and experimental venous hypertension, cuff pressure 40 mm Hg, was significantly impaired in diabetic patients as compared to the healthy subjects (p < 0. 001 vs. p < 0. 01). The maximal hyperemia after artificial arterial occlusion was significantly reduced in diabetic patients in comparison with the healthy controls (p < 0.01). Conclusions. Laser Doppler flowmetry provides a non-invasive technique for evaluating microcirculating disturbances at a relatively stage in diabetes, long before the initial clinical presentation ofperipheral arterial occlusive disease or neuropathy.
Keywords: Blood Flow Velocity; bolniki; Diabetes Mellitus, Non-Insulin-Dependent; Diabetic Angiopathies; Diabetične angiopatije; diagnostika; Foot; krvni pretok; Krvni pretok, hitrost; Laser-Doppler Flowmetry; Laser-dopplersko merjenje hitrosti pretoka; Microcirculation; Mikrocirkulacija; motnje; sladkorna bolezen; Sladkorna bolezen, ne-inzulin-odvisna; Stopalo